Building Healthcare Sector in Post-Pandemic Era: Potential Role of Islamic Social Finance - Choiriyah, Evi Aninatin Ni’matul; Mubarak, Darihan; Indrawan , Imam Wahyudi (Yayasan Mitra Peduli Indonesia, 2025)
Islamic social finance instruments can be adopted to restore and achieve a healthy life and promote welfare after COVID-19, integrated with SDGs number three. As Islamic social finance instruments, Zakat, Infaq, Sadaqah, and Waqf play a significant role in solving marginalization and vulnerability that focus on local programs, thus impacting social and economic inclusion. Using a literature review approach, the objective of this paper is to examine the role of Islamic social finance instruments as alternative funding to achieve Sustainable Development Goals (SDGs) number three,